2005
DOI: 10.1051/radiopro:2005s1-060
|View full text |Cite
|
Sign up to set email alerts
|

Soil-plant transfer of radiocaesium in weakly contaminated forest ecosystems

Abstract: Abstract. During the Chernobyl accident, large areas in Europe, particularly forests, were contaminated by radiocaesium. Soil-plant transfer is often the first step by which 137 Cs enters to food chains by incorporating the forest biogeochemical cycle. The present work is devoted to assess the soil-plant transfer of radiocaesium in weakly contaminated forest area, in the Franche-Comté region (16 202 km 2 ) in North Eastern France. This region has been markely contaminated after the Chernobyl accident. Twelve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…In previous studies, the lowest activity concentration in soil and plant organs was reported to belong to 137Cs [36]. Lamarque et al [26] monitoJapanaesethe seasonal activity concentration changes of 137Cs in Fagus sylvatica and Picea abies grown in forests, which were polluted because of the Chernobyl disaster, in Franche-Comté region in Northeastern France.…”
Section: Cs Activity Concentration Changes In Plants Treated With CD ...mentioning
confidence: 94%
See 1 more Smart Citation
“…In previous studies, the lowest activity concentration in soil and plant organs was reported to belong to 137Cs [36]. Lamarque et al [26] monitoJapanaesethe seasonal activity concentration changes of 137Cs in Fagus sylvatica and Picea abies grown in forests, which were polluted because of the Chernobyl disaster, in Franche-Comté region in Northeastern France.…”
Section: Cs Activity Concentration Changes In Plants Treated With CD ...mentioning
confidence: 94%
“…238U, a natural radionuclide, exists in nature generally in form of uranium minerals with elements such as Ca, Mg, and P. Since it has low solubility in soil solution, its intake by the plants is also at a low level. However, since its chemical behavior is similar to that of Ca, it was reported to have positive effects on metabolic reactions, in which Ca is effective [6,12,26]. In the present study, 238U activity concentrations found in leaves of Red barberry, Boxwood, and Gold tassel were found to be 168.6±20.1-223.7±26.4 1 Bq kg -1 , 171.0±20.6-265.9±31.7 1 Bq kg -1 , and 176.5±21.2-288.8±34.5 Bq kg -1 (Table 3).…”
Section: U Activity Concentration Changes and Tf Values In Plants Sub...mentioning
confidence: 99%
“…La date de référence choisie est le 1 er mai 1986, elle coïncide avec les premiers jours de l'accident du réacteur numéro 4 de la centrale nucléaire de Tchernobyl. Cette date a été retenue pour faciliter les comparaisons avec les données recueillies antérieurement sur le massif (Badot et al, 2004 ;Lamarque, 2004 ;Lamarque et al, 2005). Chaque échantillon de sol a été dosé pendant 24 h (86 400 secondes).…”
Section: Mesures D'activités En 137 Cs Dans Les éChantillons De Sol 2unclassified
“…À l'échelle de la région, la variabilité spatiale des contaminations est localement très importante tant au niveau des sols que dans la végétation. Dans l'ensemble de la partie française du massif jurassien, les activités en radiocésium dans l'horizon superficiel (0-5 cm) des sols varient entre 61 et 280 Bq.kg -1 de masse sèche (MS) et les activités massiques mesurées dans différents organes végétaux (rameaux, feuilles, aiguilles) d'essences forestières (hêtre et épicéa) présentent une grande variabilité en fonction de l'espèce, de l'organe et du type de sols et de l'amplitude des contaminations (Lamarque et al, 2005). Plusieurs facteurs sont potentiellement à l'origine de ces différences : conditions atmosphériques régnant au moment des dépôts, nature de l'occupation du sol (forêt, prairie, cultures…), type de végétation, fonctionnement du sol (régime hydrique, propriétés physicochimiques…), etc.…”
Section: Introductionunclassified
“…The biosphere and its components are under constant impact of ionizing radiation, its main sources being: radioactive substances resulting from the operation of nuclear power plants, nuclear weapon tests and accidents at nuclear power plants, cosmic radiation, etc. (Lamarque et al 2005;Butkus et al 2002Butkus et al , 2003Von Fircks et al 2002;Vaca et al 2001;Momoshima et al 1994).…”
Section: Introductionmentioning
confidence: 99%